MARKETING RESEARCH ON CONSUMER PREFERENCES FOR CRAFT BEER - Carmen-Rodica VRÎNCEANU (STOICA); Raluca Andreea ION; Marian Valentin POPESCU; Florentina MATEI; Camelia Filofteia DIGUTA; Iuliana Diana BĂRBULESCU; M (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This paper aims to explore customer preferences for craft beer through a questionnaire-based survey, analyzing key factors influencing purchasing decisions. The research focuses on aspects such as taste, aspect, alcohol content, and price sensitivity to understand the motivation behind the customer choices. The study collected responses from diverse samples of craft beer consumers, examining demographics influences on preferences. The results of the survey show that most respondents are familiar with craft beer, which they consume occasionally, usually in pubs. The bitter taste and fullness of craft beer are appreciated, they also prefer a beer made from quality ingredients with golden color, clear and glossy having a low content of alcohol packed in a glass bottle.